DEMO PENINGKATAN NILAI NUTRISI DEDAK PADI DENGAN TEKNIK FERMENTASI PADA KELOMPOK TERNAK UNGGAS DI DESA PENGOTAN, KABUPATEN BANGLI - Bidura, I.G.N.G.; Candrawati, D.P.M.A.; Wibawa, A.A.P.P.; Utami, I.A.P.; Puspani, E. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Limitations of use rice bran as a mixture of poultry rations is low protein content, easy to rancidity, and the presence of phytic acid which is capable of binding minerals Ca and P, as well as the binding protein into the phytate-protein complexes that decrease the benefits and digestibility. Hence, a ration that uses rice bran component is quite high (20-30%) should be done biotechnology processing. The purpose of this service is to improve the abilities and skills of the group members about the rice bran processing technology to improve the nutritional value of rice bran as poultry feed. The method used is through lectures and demo feed processing and preparation of rations for poultry. The results show that the activities that the coaching and training given to members of the poultry at Banjar Delod Uma, Pengotan Village, Bangli on processing techniques rice bran, soybeans-hull, and pollard as an alternative poultry feed increased by 48.06% after being given the socialization and demo (post-test scores 81.95) compared to before by socialization (pre-test scores 55.35). It can be concluded that the knowledge and skills of the group's poultry at Banjar Delod Uma, Pengotan village, Bangli increased significantly, especially in food processing and preparation of rations for poultry.